2011
DOI: 10.4238/2011.december.14.9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental factors that influence production and quality of milk of Alpine and Saanen goats

Abstract: ABSTRACT. Data from 1279 lactations of 783 Alpine and Saanen goats of the herd of our university in Minas Gerais, Brazil, were used to study environmental effects on and to estimate genetic parameters for milk production until 270 days of lactation (MP270) and for production and percentages of fat (PFAT and %FAT), protein (PPROT and %PROT), lactose (PLACT and %LACT), and total dry extract (PEXTR and %EXTR). Environmental effects were estimated by a statistical model that included contemporary group effect, typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
3
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 20 publications
3
14
3
3
Order By: Relevance
“…As a result, goats delivering multiple kids had greater CMY (+35 L) than goats delivering single kids (Table 3). Our findings agree with those of several authors who found a higher milk production in multiple deliveries in commercially milked goats (Browning et al, 1995;Crepaldi et al, 1999;Brito et al, 2011). Litter size is positively associated with antepartum levels of mammogenic hormones such as placental lactogen, progesterone, and prolactin (Lérias et al, 2014).…”
Section: Milk Yieldsupporting
confidence: 92%
“…As a result, goats delivering multiple kids had greater CMY (+35 L) than goats delivering single kids (Table 3). Our findings agree with those of several authors who found a higher milk production in multiple deliveries in commercially milked goats (Browning et al, 1995;Crepaldi et al, 1999;Brito et al, 2011). Litter size is positively associated with antepartum levels of mammogenic hormones such as placental lactogen, progesterone, and prolactin (Lérias et al, 2014).…”
Section: Milk Yieldsupporting
confidence: 92%
“…Genetic correlations between SCS and fat, protein or lactose contents obtained by Lindmark-Månsson et al (2006) for dairy cattle were different from those obtained in our study (-0.050, 0.393 and -0.774, respectively), but correlation between logSCC and protein content in dairy sheep was closer to our result (0.37 vs 0.54; Baro et al, 1994). The genetic correlation between milk yield and lactose content estimated by Brito et al (2011) in the Brazilian population is different from our result (0.15 vs -0.46).…”
Section: Resultscontrasting
confidence: 52%
“…Similar heritability (0.35) was presented by Morris et al (2011) but for lactose yield. However, the lactose content found by Brito et al (2011) was much lower (0.17) than that presented in our and Andonov et al (2007) studies. In the literature different results for lactose content in cow's milk are presented -from 0.17 to 0.36, depending of the stage of lactation and parity with the lowest at the beginning of the first lactation (Ptak et al, 2012) up to an average heritability of 0.48 in the first, and 0.51 in the second and later parities (Miglior et al, 2007).…”
Section: Resultscontrasting
confidence: 50%
See 1 more Smart Citation
“…RRMs have the advantage of not only being able to deal with a greater volume of data, but also result in a greater detailing of the phenotype, which allows for more accurate estimates of the genetic values. Brito et al (2011) and Silva et al (2013a) assessed fixed effects that affect CMY and TDMY, respectively. The former demonstrated that fixed effects should be included in singletrait, multi-trait, and repeatability models, whereas the latter demonstrated that fixed effects should be included in RRMs.…”
Section: Introductionmentioning
confidence: 99%